The degradability by sheep of fruits of acacias and leaves of Sesbania sesban and the effects of supplementation with mixtures of browses and oilseed cake on the utilization of teff (Eragrostis tef) straw - Nsahlai, I.V.; Osuji, P.O.; Umunna, N.N. (Cambridge University Press, 1995)
This study was aimed at evaluating (1) the dry matter (DM) and nitrogen (N) degradabilities (by sheep) of Sesbania sesban leaves, Acacia albida (Faidhabia albida), A. siberiana and a. tortilis fruits and (2) the effect of feeding a mixture of oilseed cake and tanniferous browses on the degradability of teff (Eragrostis tef) straw and oilseed cake and on particulate and liquid passage rates. Thirteen rumen cannulated sheep in a randomized complete-block design experiment were given teff straw ad libitum supplemented (DM per day) with 155 g oilseed cake (50:50 mixture of noug (Guizotia abyssinica) and groundnut cake; oilseed cake diet) or with 92 g oilseed cake plus either 118 g S. sesban (sesbania diet) or 179 g A. albida fruits (albida diet). Diets were formulated to supply 10.5 g supplementary N per day. Sesbania had the highest DM washing loss, potential degradability and fastest DM degradation rate compared with the acacias. The N washing loss (g/kg) was highest for A. siberiana (500) followed by A. albida (431), A. tortilis (431) and sesbania (241). The potential N degradability (g/kg) was greater (<0.05) for sesbania (978) than for A. albida (848), A. tortilis (865) or A. siberiana (785). The degradation rates of oilseed cake-N and teff straw-DM, particulate and liquid passage rates, basal intake and DM digestibilities were similar among diets, but organic matter intake was highest for the albida diet. At the present levels of offer, supplementation with mixtures of oilseed cake and browses does not significantly reduce rumen degradation rates of oilseed cake-N or teff straw DM.